The Influence of Work Motivation and Job Satisfaction on Teacher Performance Yayasan Dharma Setia Kosgoro Kota Bogor - Elbie Yudha Pratama; Dian Indiyati; Ratri Wahyuningtyas (International Journal of Science, Technology & Management, 2026)
Dharma Setia Kosgoro Bogor City Foundation (YDSK) is an educational foundation established in 1987 that oversees three educational units, namely SMP Kosgoro, SMA Kosgoro, and SMK Kosgoro. As a private educational institution, the foundation faces challenges related to the uneven performance of teachers across its three educational units. An analysis of the Teacher Performance Assessment (PKG) document for the 2020/2021 academic year revealed an average score of 91.07%, categorized as "Very Good." However, gaps were identified in the social and professional competency aspects, which remained in the "Good" category with a score of 75%. This condition requires a deeper examination of the factors influencing teacher performance, particularly work motivation and job satisfaction, in order to generate targeted policy recommendations for the foundation's management. This study aims to analyze and empirically examine the effect of Work Motivation (X1) and Job Satisfaction (X2) on Teacher Performance (Y) at Yayasan Dharma Setia Kosgoro Bogor City. This study employed a quantitative approach with a survey method using questionnaires, involving all teachers from the three educational units under the foundation as the study population. The collected data were processed using descriptive analysis techniques with SEM-PLS. Based on the findings of this study, it can be concluded that Job Satisfaction is the primary determinant of Teacher Performance at Yayasan Dharma Setia Kosgoro Bogor City, while Work Motivation was not proven to have a statistically significant effect, although the direction of the relationship was positive. The foundation's management is advised to prioritize efforts to improve teacher job satisfaction through the implementation of a fair and competitive compensation system, the creation of a conducive work environment, the provision of recognition for teacher dedication and achievement, and the provision of continuous professional development opportunities. Future research is recommended to expand the scope of variables by incorporating other factors such as transformational leadership, organizational commitment, or organizational culture, in order to obtain a more comprehensive understanding of the determinants of teacher performance in the context of private foundation education.